The Impact of Risk Factors in Practice on Anxiety Level of Nursing Students (Sample of Nevsehir Province) - Nilgün Ulutaşdemir; Ozan Şahan; Hasan Tuna (Association of Nurse Managers, 2020)
INTRODUCTION: This descriptive study was realized to determine the hazards and risk encountered by the nursing students during clinical practise and to identify their effects on anxiety levels. METHODS: The population of this cross-section, descriptive study consisted of nursing students (N: 353 persons) in the second, third and fourth years at university in October-November 2017. The whole population was included in the study, and except for the students who dint participate during the lessons and who refused taking part in the survey 288 participants were included in the study. The data of study were collected using a questionnaire including socio-demographic characteristics, risks and hazards arising from environment, Health Worker Safety Scale and Beck Anxiety Scale in the classroom situation. The data were analyzed by using frequency, t test, ANOVA and correlation. RESULTS: The Beck Anxiety Scale mean scores of those satisfied with the hospital were found to be higher than that of those unsatisfied. The Health Workers' Safety Scale mean scores of those who worked and were satisfied with the hospital were found to be higher than that of those unsatisfied. DISCUSSION AND CONCLUSION: This study was found that the students had occupational safety but experienced moderate anxiety.